PENGARUH KEARIFAN LOKAL TERHADAP SIKAP MODERASI BERAGAMA ISLAM PADA MASYARAKAT MULTIKULTURAL - Irfan Jaenal Abidin; Indah Maharani; Ahmad Fauzi; Abdul Ghofur (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the influence of local wisdom on Islamic religious moderation attitudes in multicultural societies. The research employed a quantitative approach using an explanatory survey design. Data were collected through questionnaires distributed to respondents from Muslim communities living in multicultural environments. The research instrument was developed based on indicators of local wisdom and Islamic religious moderation attitudes, and the data were analyzed using descriptive statistics and simple linear regression analysis with the assistance of SPSS software. The results indicate that local wisdom has a positive and significant effect on Islamic religious moderation attitudes. Values of local wisdom such as tolerance, mutual cooperation, deliberation, and respect for differences contribute to the development of moderate, inclusive, and balanced religious attitudes. Therefore, local wisdom plays a strategic role as social capital in strengthening religious moderation and maintaining social harmony within multicultural societies.